Does Dividend Announcement Generate Market Signal? Evidence from Pakistan - Chaudhary, Ghulam Mujtaba; Hashmi, Shujahat Haider; Younis, Shahzada Aqeel (International Journal of Economics and Financial Issues, 2016)
This study is aimed at investigating the signaling effect of cash dividend announcements by employing the standard event methodology over the companies listed on Karachi Stock Exchange. The companies are randomly selected from different sectors that have announced cash dividends during calendar year 2010 and total 30 companies are included in the study. The standard event methodology is applied to explore the impact of cash dividend announcements upon stock returns and an event window of 15 days with dividend announcement date as the event day is constructed. The results show that the average abnormal returns, by and large, remained positive and statistically significant in post-event window days. The results of study tend to support dividend signaling hypothesis indicating that the dividend announcement may be used as a tool to generate positive signals in the market. Keywords: Dividend Announcements, Event Window, Abnormal Returns and t-Test JEL Classifications: F65; G2